2007
DOI: 10.1038/nphys543
|View full text |Cite
|
Sign up to set email alerts
|

Electrical detection of spin transport in lateral ferromagnet–semiconductor devices

Abstract: A longstanding goal of research in semiconductor spintronics is the ability to inject, modulate, and detect electron spin in a single device 1-4 . A simple prototype consists of a lateral semiconductor channel with two ferromagnetic contacts, one of which serves as a source of spin-polarized electrons and the other as a detector. Based on work in analogous metallic systems 5-8 , two important criteria have emerged for demonstrating electrical detection of spin transport. The first is the measurement of a non-e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

33
703
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 786 publications
(754 citation statements)
references
References 34 publications
33
703
3
2
Order By: Relevance
“…In the Datta-Das device, the spinpolarized current which flows in the semiconductor channel, often supposed as a 2-dimensional electron gas (2DEG), is manipulated by electrostatic gate-action, hence providing electrical control of the source-drain current in addition to that provided by the relative alignment of the ferromagnetic contacts. To this end, imaging of the injected spin-polarization from Fe into n-GaAs has been performed in a lateral geometry by Crooker et al 11 and in a cross-sectional geometry by Kotissek et al 12 , whilst Lou et al 13 and Lou et al 14 have demonstrated all-electrical measurements of spin-injection, -transport and -detection in a single Fe/GaAs(001) device. Garlid et al 15 have also used Fe/InGaAs(001) contacts to measure the transverse spin-current generated via the spin-Hall effect.…”
Section: Introductionmentioning
confidence: 99%
“…In the Datta-Das device, the spinpolarized current which flows in the semiconductor channel, often supposed as a 2-dimensional electron gas (2DEG), is manipulated by electrostatic gate-action, hence providing electrical control of the source-drain current in addition to that provided by the relative alignment of the ferromagnetic contacts. To this end, imaging of the injected spin-polarization from Fe into n-GaAs has been performed in a lateral geometry by Crooker et al 11 and in a cross-sectional geometry by Kotissek et al 12 , whilst Lou et al 13 and Lou et al 14 have demonstrated all-electrical measurements of spin-injection, -transport and -detection in a single Fe/GaAs(001) device. Garlid et al 15 have also used Fe/InGaAs(001) contacts to measure the transverse spin-current generated via the spin-Hall effect.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that electronic spin transport in bulk semiconducting systems at high temperatures is very rare. For instance, spin transport in GaAs-based spin valves is observable only up to 70 K 41 . Similarly, spin transport in Si-based spin valves in a non-local geometry was observable only at temperatures below 150K 33 .…”
mentioning
confidence: 99%
“…[1][2][3][4] For improving the Spin-field effect transistor (FET) characteristics, high spin injection efficiency and strong spin orbit (SO) interactions are desirable. So far a number of spin injection and detection in ferromagnetic metal/semiconductor hybrid structures have been examined in various methods, such as circular polarization detection from spin light emitting diode [5][6] , electrical spin accumulation detection in nonlocal geometry [7][8][9] and so on. Among them, nonlocal spin valve measurement has been widely used for electrical spin injection and detection measurements which is free from the influence of anisotropic magnetic resistance (AMR) and local Hall effect.…”
mentioning
confidence: 99%